Experimental and theoretical evaluation of punching strength of steel fiber reinforced concrete slabs. (15th November 2017) - Gouveia, Nuno D.; Lapi, Massimo; Orlando, Maurizio; Faria, Duarte M. V.; Ramos, António M. P
Abstract : This paper deals with the experimental and theoretical evaluation of punching shear capacity of steel fiber reinforced concrete (SFRC) slab–column connections. Five experimental specimens with a thickness of 160 mm, different fiber volume contents (0, 1.0, and 1.5%) and different flexural reinforcement ratios (0.75 and 1.5%) have been tested. The experimental results were evaluated using a physical–mechanical model based on the critical shear crack theory (CSCT). The model has given a good approximation of experimental punching shear strengths. In general, tests have highlighted a significant increase in load and deformation capacity of fiber reinforced concrete slab–column connections in comparison with reinforced concrete connections.